ANALISIS PERKERASAN LENTUR PADA RUAS JALAN HONIMUASAPARUA TIMUR KABUPATEN MALUKU TENGAH - Sahupala, Azani Subhi; Siahaya, Vera Th. C.; Lewakabessy, Godfried (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The Honimua-East Saparua Road section is a road section located in East Saparua District, Central Maluku Regency, Maluku Province. This road section was completed in 2015. With a total road length of 3 km and a road width of 4 m. Meanwhile, currently the condition of the Honimua–East Saparua road section is experiencing quite serious damage, the causes include, among other things, flooding on the road section, coupled with the absence of road preservation carried out by the government on the Honimua–East Saparua road section, resulting in damage to This section of road is increasingly worrying. Based on the priority order value of the road, the Honimua road is included in the periodic maintenance program. The remaining life of the road plan uses the AASTHO method with a percentage reduction in the remaining life of the plan of 6.60%. Based on the results of planning the thickness of the road pavement for resurfacing the road surface for the condition of the Honimua - East Saparua Road, Central Maluku Regency with a design age of 10 years, the following are obtained: AC – WC = 40 mm, AC – BC = 60 mm, AC – Base = 0 mm, LPA Class A = 400 mm.